Fluidodinâmica computacional da descarga marinha de Solução hipersalina - Ximenes, Levi de Brito (2021)
The growing demand for drinking water on the planet generates the need for the development of technologies capable of converting water unsuitable for distribution, such as sea water, into water suitable for supply. Desalination is one of these technologies. Aiming an alternative to the public supply, the Water and Sewage Company of the State of Ceará (CAGECE) launched a public notice for the implementation of a desalination plant. With the desalination process, a hypersaline solution is generated as waste, which is dumped into the sea through diffusers. Due to the density difference between the fluids, the outflow is divided into two regions: ascending jet, with large momentum; and descending fountain, where the flow is governed by the negative buoyancy. Given the scarcity of numerical simulations for the discharge and dispersion of hypersaline solutions, this research presents a computational fluid dynamics (CFD) modeling of jets and fountains, through the FLUENT software, focusing on the project conditions presented for the desalination plant in Fortaleza. The model was compared to the data available in the literature and then simulated for the characteristics of the CAGECE desalination plant, considering a single diffusor in stagnant environment. In addition, the results were compared to those obtained through simulations with the integral VISUAL PLUMES software for different discharge angles (30°, 45°, 60° and 90°). The results showed good agreement with published works, generating the equation Zm/r0 = 1.71(Fr), which is able to predict the height reached by the jets/fountains (Zm), informing the diffuser radius (r0) and the Froude number (Fr) The CFD simulations were similar to those obtained with VISUAL PLUMES.